Why Global North criminology fails to explain organized crime in Mexico - Pereda, Valentin (Theoretical criminology, 2022)
The prevailing definitions of organized crime and methodological approaches to studying it derive mainly from the Global North. However, an emergent body of literature suggests that organized crime in the Global South differs from organized crime in the Global North. Focusing on the case of Mexico, I argue that mainstream criminological theories’ inability to explain significant aspects of organized crime in that country stems from their underspecified scope. Mainstream theories analyse organized crime as a phenomenon that transpires in societies characterized by high levels of internal peace, rule of law and strong public institutions. In Mexico, a country that fails to adhere to these conditions, organized crime manifestations defy prevailing theoretical assumptions.